Recombinant polymerase amplification combined with lateral flow strips for the detection of deep-seated Candida krusei infections - Zhao, Mengdi; Wang, Xizhen; Wang, Kun; Li, Yuanyuan; Wang, Yan; Zhou, Ping; Wang, Lei; Zhu, Wenjun (Frontiers in Cellular and Infection Microbiology, 2022)
The incidence of Candida infections in intensive care units (ICU) has increased significantly in recent years, and has become one of the most serious complications threatening the lives of ICU patients. In particular, the proportion of non-Candida albicans infections, such as Candida krusei and Candida glabrata, which are resistant to fluconazole, has been increasing each year. The early diagnosis of the strains of Candida infections is important for the timely implementation of targeted treatments that save patients' lives. However, the current application of direct microscopy, culture, and histopathology, as well as other diagnostic methods have many shortcomings such as their low sensitivity and time requirements, which cannot meet the needs of early clinical diagnoses. Recombinant polymerase amplification (RPA) is a promising isothermal amplification technique with a low dependence on instruments and equipment, and is suitable in resource-poor areas. RPA combined with lateral flow strips (LFS) can rapidly amplify and visualize target genes within 20 min. In this study, RPA-LFS was used to amplify the internal transcribed spacer region 2 (ITS2) gene of C. krusei, and the primer-probe design was optimized by introducing base mismatches (probe modification of five bases) to obtain a specific and sensitive primer-probe combination for the detection of clinical samples. Twenty-four common clinical pathogens were tested using RPA-LFS to determine the specificity of the detection system. The gradient dilution of the template was tested to explore the lower limit of detection (LOD) of the assay and to determine the sensitivity of the assay. The RPA-LFS and qPCR assays were performed on 189 clinical samples to evaluate the detection performance of the RPA-LFS system, to provide a reliable molecular diagnostic method for the detection of C. krusei, and to meet the urgent need for rapid, specific, sensitive and portable clinical field testing.